'A new species of mony': British Exchequer bills, 1701-1711. (18th September 2015) - Kleer, Richard A.
Abstract : This article studies the relationship between Bank and Treasury during the War of the Spanish Succession. It examines two new series of Exchequer bills implemented in 1707 and 1709. Far from being loans-for-rents contracts, the principal aim was to accommodate war-related pressures on the nation's monetary system by manufacturing a substitute for scarce specie. The article also shows there was a covert struggle within the financial community for access to the specie flows associated with the nation's system of public finance.